High-Throughput Analyses of Microplastic Samples Using Fourier Transform Infrared and Raman Spectrometry. Issue 9 (September 2020) - Brandt, Josef; Bittrich, Lars; Fischer, Franziska; Kanaki, Elisavet; Tagg, Alexander; Lenz, Robin; Labrenz, Matthias; Brandes, Elke; Fischer, Dieter; Eichhorn, Klaus-Jochen
Determining microplastics in environmental samples quickly and reliably is a challenging task. With a largely automated combination of optical particle analysis, Fourier transform infrared (FT-IR), and Raman microscopy along with spectral database search, particle sizes, particle size distributions, and the type of polymer including particle color can be determined. We present a self-developed, open-source software package for realizing a particle analysis approach with both Raman and FT-IR microspectroscopy. Our software GEPARD (Gepard Enabled PARticle Detection) allows for acquiring an optical image, then detects particles and uses this information to steer the spectroscopic measurement. This ultimately results in a multitude of possibilities for efficiently reviewing, correcting, and reporting all obtained results.